Systematic position of Australian genus Palaeoscydmaenus Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2012)
The Australian monospecific genus Palaeoscydmaenus Franz is revised based on the type material of P. australiensis Franz. The original placement of Palaeoscydmaenus in the tribe Scydmaenini is regarded as erroneous and evidence is provided to support a formal transfer of this genus to Cyrtoscydmini. Diagnostic characters of Scydmaenini and Cyrtoscydmini are discussed, Palaeoscydmaenus is redefined, and P. australiensis is redescribed.